PEMETAAN (MAPPING) POTENSI DIRI INDIVIDU (PERFORMANCE) DENGAN METODE PRIBADI SPIDER PLOT PADA PEGAWAI PEJABAT STRUKTURAL DAN FUNGSIONAL DI PT. XYZ (BUMN) DAN PEMDA X DI JAWA TIMUR - Pribadiyono Pribadiyono (EKUITAS (Jurnal Ekonomi dan Keuangan), 2004)
A Company which focal are efficiency and effectiveness, will make an effort to manage their human resources. Appropriately allocated human resources can be done by means of pronouncing a prerequisite as a standard attribute which should be possesed by employee applicant. Hence, an evaluation toward individuals 'performance is expected capable to carry out task from the companies.One of latest method which can be used to evaluate staff 'performance is Pribadi Spider Plot, and resembles a method which illustrate mapping of individual's observation (strength and weaknes). Generally, Individual's performance evaluation based on standard psychological test as a reference to evaluate performance when will be promoted or during fresh staff recruitment. However, there are another managements attribut es which  was not detected, where inaccuracy  in evaluating Individual 's performance will Lake place. Pribadi Spider Plot Model will complete these inadequacies, where Lhis method will unite psychological test and management test and will be assembled with weighting method rating and scoring.Through the result of psycho  test and management  test which conducted in PT. XYZ Surabaya, as one of Federal Corporation in Indonesia, and District X  located around Gerbang Kertosusilo,  has not yet  been attained companies standard performance score of 313.76 and total rating of 37.40. Still, the highest total score result attained from psycho  Lest and management test conducted in PT  XYZ of 268.65 with total ratings of 31.18. Andfrom the District X located around Gerbang Kertosusilo, the highest score result merely of 258.04 with tolal ratings of 23.50. By achieving individual's total score and total ratings through psychological and management Test, companies will have capability of accepting or rejecting these staffs. Companies management department will be able to plan their staff’s career, settlement or mutation based on their ability and skill.